Somatoform disorders. Models of personification oriented therapy - O. Kudinova; B. Mykhaylov; T. Chorna (European Psychiatry, 2022)
Introduction Contemporary in Ukraine the special priority has been the somatoform disorders increase. The most significant complications belong to the patient’s self-evaluation of the influence of the disease on their social functioning, influence essential part of the self-evaluation of the disease and the important point of therapeutic personality accomodate intervention.